Caspase-3 Cleaves Extracellular Vesicle Proteins During Auditory Brainstem Development - Weghorst, Forrest; Mirzakhanyan, Yeva; Samimi, Kian; Dhillon, Mehron; Barzik, Melanie; Cunningham, Lisa L.; Gershon, Paul D.; Cramer, Karina S. (Frontiers in Cellular Neuroscience, 2020)
Sound localization requires extremely precise development of auditory brainstem circuits, the molecular mechanisms of which are largely unknown. We previously demonstrated a novel requirement for non-apoptotic activity of the protease caspase-3 in chick auditory brainstem development. Here, we used mass spectrometry to identify proteolytic substrates of caspase-3 during chick auditory brainstem development. Functional annotation analysis revealed that our caspase-3 substrates were enriched more than two-fold for proteins associated with extracellular vesicles (EVs), membrane-bound nanoparticles that function in intercellular communication. The proteome of EVs isolated from the auditory brainstem contained caspase-3 and was highly enriched for the caspase-3 substrates identified here. Additionally, we identified two caspase-3 substrates with known functions in axon guidance, namely Neural Cell Adhesion Molecule (NCAM) and Neuronal-glial Cell Adhesion Molecule (Ng-CAM), that were found in auditory brainstem EVs and expressed in the auditory pathway alongside cleaved caspase-3. Taken together, these data suggest a novel developmental mechanism whereby caspase-3 influences auditory brainstem circuit formation through the proteolytic cleavage of EV proteins.